Disrupting Discipline: A DisCrit Critique of Behavior “Management” in the Art Room - Gabriel, Jenna (Research in Arts and Education, 2022)
Utilizing a required training module on restraint and seclusion as an example for analysis, this article employs a Disability Critical Race Theory (DisCrit) lens to critique dominant classroom management practices that negatively and disproportionately affect disabled students, particularly disabled students of color. This article suggests that critical disability studies holds potential for informing counter-practice in the art classroom, connecting the radical politics of Disability Art with resistance to special education’s influence on art pedagogy. In suggesting disability studies as an alternative paradigm to inform art education, the article concludes by proposing art teachers can disrupt school-based cycles of harm.